2015
DOI: 10.3389/fmicb.2015.00116
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic degradation of cyclohexane by sulfate-reducing bacteria from hydrocarbon-contaminated marine sediments

Abstract: The fate of cyclohexane, often used as a model compound for the biodegradation of cyclic alkanes due to its abundance in crude oils, in anoxic marine sediments has been poorly investigated. In the present study, we obtained an enrichment culture of cyclohexane-degrading sulfate-reducing bacteria from hydrocarbon-contaminated intertidal marine sediments. Microscopic analyses showed an apparent dominance by oval cells of 1.5 × 0.8 μm. Analysis of a 16S rRNA gene library, followed by whole-cell hybridization with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 66 publications
3
26
0
Order By: Relevance
“…The reaction is catalyzed by glycyl-radical enzymes [Heider et al,this volume,. Since its first description, activation by addition to fumarate has been frequently demonstrated for the degradation of n -alkanes and cycloalkanes under nitrate-and sulfate-reducing conditions [Callaghan, 2013;Heider and Schühle, 2013;Jaekel et al, 2015;Musat et al, 2010;Rabus, 2005;. In addition, recent genome analyses suggested that a similar mechanism of activation may be employed in methanogenic enrichment cultures with n -alkanes [Embree et al, 2014;Tan et al, 2013Tan et al, , 2014.…”
Section: Overview Of the Mechanisms Of Activation For Gaseous Alkanesmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction is catalyzed by glycyl-radical enzymes [Heider et al,this volume,. Since its first description, activation by addition to fumarate has been frequently demonstrated for the degradation of n -alkanes and cycloalkanes under nitrate-and sulfate-reducing conditions [Callaghan, 2013;Heider and Schühle, 2013;Jaekel et al, 2015;Musat et al, 2010;Rabus, 2005;. In addition, recent genome analyses suggested that a similar mechanism of activation may be employed in methanogenic enrichment cultures with n -alkanes [Embree et al, 2014;Tan et al, 2013Tan et al, , 2014.…”
Section: Overview Of the Mechanisms Of Activation For Gaseous Alkanesmentioning
confidence: 99%
“…The anaerobic degradation of n -and branched alkanes has been demonstrated also with enriched and pure cultures of nitrate-reducing bacteria [for an overview see . The anaerobic degradation of cycloalkanes, which generally received less attention than the n -alkanes, was demonstrated with sulfate-reducing [Jaekel et al, 2015;Rios-Hernandez et al, 2003] and nitrate-reducing enrichment cultures . In addition, conversion of alkanes to methane was shown with enrichment cultures using single n -alkanes or crude oil as substrates [Jones et al, 2008;Zengler et al, 1999].…”
Section: Biodegradation Of Gaseous Alkanes and Ethylbenzenementioning
confidence: 99%
“…For example, Matilla, et al [138] found that A. thaliana produce distinct patterns of root exudation when it grows with and without Pseudomonas putida KT2440. In addition, when the biocontrol strain Pseudomonas WCS365 is added in sufficient quantity for the biocontrol to operate, organic acids (citric acid especially) is strongly increased, while the amount of succinic acid drastically decreased [225].…”
Section: Root Exudation the Ecological Driver Of Microbial Communitimentioning
confidence: 99%
“…Anaerobic degradation has also been coupled to methanogenesis, fermentation and phototrophic metabolism but growth of these microorganisms and as a result, biodegradation rates are significantly lower compared to aerobic degraders. Despite not often being considered as aerobic bacteria, there is an increasing interest in the use of anaerobic bacteria for bioremediation [17,[135][136][137][138].…”
Section: Hydrocarbon Rhizoremediationmentioning
confidence: 99%
“…Overall, these studies have demonstrated that n -alkanes with a chain length from C 3 up to at least C 20 can be degraded under anoxic conditions (although apparently no example of npentane utilization under anoxic conditions has been reported so far). Besides n -alkanes, microorganisms are also capable of degrading branched [Bregnard et al, 1997;Grossi et al, 2000] and cyclic [Jaekel et al, 2015;Musat et al, 2010;Rios-Hernandez et al, 2003] alkanes under strictly anoxic conditions. The apparent widespread occurrence of anaerobic degraders of aliphatic hydrocarbons has prompted numerous studies to establish their physiologies, metabolic capabilities and metabolic pathways.…”
mentioning
confidence: 99%